REDUCTION IN SEEPAGE RATE AND STORAGE CAPACITY OF A DUGOUT POND-A CASE STUDY - Ranade, D.H.; Tomar, A.S.; Jain, L.K.; Vishwakarma, S.K. (Journal of Soil and Water Conservation, 2022)
In a study, it was observed that the seepage rate from a dugout pond was reduced to 7 cm day -4 after a span of 12 years from the original seepage rate of 12 cm day-1. This was due to the natural silting in the tank area. However; it was observed that the reduction in storage capacity at higher rate was mainly because of excess siltation due to dismantling of inlet concrete structure.